1998
DOI: 10.1007/s004649900648
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mechanism of increased intracranial pressure with insufflation

Abstract: This study suggests that care may be needed with laparoscopy in patients at risk for increased ICP due to head injury or a space occupying lesion. The mechanism of increased ICP associated with insufflation is most likely impaired venous drainage of the lumbar venous plexus at increased intraabdominal pressure. Further studies of cerebral spinal fluid movement during insufflation are currently underway to confirm this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(84 citation statements)
references
References 19 publications
1
78
0
5
Order By: Relevance
“…3 In addition, previous studies have reported that it causes a significant reduction of cerebral tissue oxygen saturation (Sct O 2 ) in elderly patients 4 and in patients with pre-existing raised intracranial pressure (ICP). 5 Patients presenting for robotic surgery are usually elderly, and are thus patients in whom the procedure may upset the critical balance between cerebral oxygen supply and demand.…”
mentioning
confidence: 99%
“…3 In addition, previous studies have reported that it causes a significant reduction of cerebral tissue oxygen saturation (Sct O 2 ) in elderly patients 4 and in patients with pre-existing raised intracranial pressure (ICP). 5 Patients presenting for robotic surgery are usually elderly, and are thus patients in whom the procedure may upset the critical balance between cerebral oxygen supply and demand.…”
mentioning
confidence: 99%
“…Likewise, there are studies that reported that the gas used to augment the severity of bacteriemia plays only a minor role. [47] In conclusion, in the rats with peritonitis, the CO 2 pneumoperitoneum, compared to laparotomy, resulted in a less severe inflammatory response and peritonitis. Therefore, we think that in the cases of generalized peritonitis, surgical procedures for diagnosis and treatment can be carried out successfully, and that this point will be highlighted more by randomized controlled clinical studies for the said purposes.…”
Section: Discussionmentioning
confidence: 83%
“…The combination of steep Trendelenburg and pneumoperitoneum, used in robotic-assisted MIS has been shown increase mean arterial blood pressure, as well as right and left ventricular filling pressures, and pulmonary capillary wedge pressure in both healthy patients and in those with cardiopulmonary disease [17]. In addition, pneumoperitoneum and head-down tilt have both been found to induce intracranial hypertension [18], and in elderly patients to reduce cerebral tissue oxygen saturation [19]. Whether or not these physiologic changes can lead to cardiovascular or neurologic injury in elderly patients undergoing long robotic-assisted MIS procedures has not been well established.…”
Section: Discussionmentioning
confidence: 99%